(untitled) (The Pakistan Development Review, 1997)
Pakistan for many years maintained strict controls on foreign direct investment. However, over the past decade controls on foreign investment in manufacturing have diminished sharply, though less so for the service sector. The government continues to impose restrictions on foreign trade, which adversely affect foreign direct investors in several ways. Nonetheless, Pakistan has moved a substantial distance toward liberalising direct foreign investment. There are two obvious policy issues related to foreign investment raised by these developments. First, should Pakistan proceed further toward liberalisation and at what pace? Second, with a liberalised investment sector, should Pakistan become an active protagonist among developing countries for a multilateral agreement on investment?